HUBUNGAN USIA DAN PARITAS IBU BERSALIN DENGAN KEJADIAN RETENSIO PLASENTADI RSUD RADEN MATTAHER PROVINSI JAMBI TAHUN 2018 - Sulastri Sulastri (MIDWIFERY HEALTH JOURNAL, 2019)
The high maternal mortality rate is a major problem that occurs in the health sector. The maternal mortality rate in Indonesia is still the highest in ASEAN. Childbirth is a highly anticipated thing for pregnant women. But in labor and after childbirth is a prone for mothers to experience bleeding that is so great. The main causes of maternal death in Indonesia were 67% bleeding (uterine atony by 22.88%, residual placenta at 19.40%, placental retention of 40.30%, and labor with birth canal laceration of 16.42%). Bleeding occurs 10 times more often during labor (Arifin, 2012).The purpose of this study was to determine the relationship of age and maternal parity with the incidence of placental retention in Raden Mattaher Regional General Hospital Jambi Province in 2019.The results showed that there was a relationship between age and incidence of retention of placenta in Raden Mattaher General Hospital in Jambi Province with a p value of 0.001 and there was no relationship between parity and the incidence of retention of placenta in RSUD Raden Mattaher Jambi Province, p value 0.102. It is expected that the results of this study are expected to be used as information material to prevent early occurrence of placental retention, because most of the incidence of placental retention can be predicted beforehand.